Gastritis in medical students: An analysis of contributing factors - Kesuma, Farah Shyfa; Girsang, Ermi; Nasution, Ali Napiah (Buletin Kedokteran & Kesehatan Prima, 2024)
Gastritis, defined as inflammation of the stomach lining, can arise from various factors, including Helicobacter pylori infection, stress, poor dietary habits, and the use of certain medications. Medical students represent a population particularly susceptible to gastritis due to high academic pressure, irregular eating patterns, and smoking habits. This study aimed to analyze the risk factors for gastritis among medical students at Prima Indonesia University. This study employed a cross-sectional design involving 123 medical students. Data were collected through questionnaires, and statistical analysis was performed using SPSS version 27. The majority of the study subjects were 21 years old (61.8%) and female (74.8%). Irregular eating habits (82.1%), coffee consumption (74%), and academic stress (79.7%) were prevalent among the subjects. More than half of the subjects had a history of gastritis (57.7%). The risk factors significantly associated with gastritis included female sex (OR=2.362; 95% CI: 1.030-5.414), irregular eating patterns (OR=3.707; 95% CI: 1.385-9.918), coffee consumption (OR=2.569; 95% CI: 1.126-5.861), and academic stress (OR=3.062; 95% CI: 1.227-7.638). Age did not significantly affect the risk of gastritis. Females were found to be more susceptible to gastritis than males, possibly due to hormonal influences and lifestyle factors. Irregular eating patterns and coffee consumption increased the risk of gastritis; however, smoking habits did not show a significant association. Academic stress was identified as an important risk factor, as it can increase gastric acid production. The risk factors significantly associated with gastritis among medical students were female sex, irregular eating patterns, coffee consumption, and academic stress.